Solamargine inhibits the growth of hepatocellular carcinoma and enhances the anticancer effect of sorafenib by regulating HOTTIP‐TUG1/miR‐4726‐5p/MUC1 pathway. Issue 4 (17th January 2022) - Tang, Qing; Li, Xiaojuan; Chen, Yun; Long, Shunqin; Yu, Yaya; Sheng, Honghao; Wang, Sumei; Han, Ling; Wu, Wanyin
Abstract: Hepatocellular carcinoma (HCC) is one of the most common primary malignancies. Drug resistance has significantly prevented the clinical application of sorafenib (SF), a first‐line targeted medicine for the treatment of HCC. Solamargine (SM), a natural alkaloid, has shown potential antitumor activity, but studies about antitumor effect of SM are obviously insufficient in HCC. In the present study, we found that SM significantly inhibited the growth of HCC and enhanced the anticancer effect of SF. In brief, SM significantly inhibited the growth of HepG2 and Huh‐7 cells. The combination of SM and SF showed a synergistic antitumor effect. Mechanistically, SM downregulated the expression of long noncoding RNA HOTTIP and TUG1, followed by increasing the expression of miR‐4726‐5p. Moreover, miR‐4726‐5p directly bound to the 3′‐UTR region of MUC1 and decreased the expression of MUC1 protein. Overexpression of MUC1 partially reversed the inhibitory effect of SM on HepG2 and Huh‐7 cells viability, which suggested that MUC1 may be the key target in SM‐induced growth inhibition of HCC. More importantly, the combination of SM and SF synergistically restrained the expression of MUC1 protein. Taken together, our study revealed that SM inhibited the growth of HCC and enhanced the anticancer effect of SF through HOTTIP‐TUG1/miR‐4726‐5p/MUC1 signaling pathway. These findings will provide potential therapeutic targets and strategies for the treatment of HCC. Abstract : In vitro and in vivo results showed that solamargine (SM) significantly inhibited the growth and enhanced the antitumor effect of sorafenib by regulating the HOTTIP‐TUG1/miR‐4726‐5p/MUC1 signaling pathway in hepatocellular carcinoma (HCC). In brief, SM significantly downregulated the expression of long noncoding RNA HOTTIP and TUG1. Overexpression of HOTTIP and TUG1 decreased miR‐4726‐5p and reversed the effect of SM‐increased expression of miR‐4726‐5p through acting the sponges of miR‐4726‐5p. Moreover, miR‐4726‐5p directly bound to the 3′‐UTR region of MUC1, followed by reducing the expression of MUC1 protein. On the other hand, SM drastically decreased the promoter activity and protein expression of MUC1, overexpression of MUC1 significantly reversed the inhibitory effect of SM on HCC cells. More importantly, the combination of SM and sorafenib have a remarkable synergy on the downregulation of MUC1 and growth inhibition of HCC. Therefore, MUC1 may be the criticaltarget in the SM‐induced growth inhibition and the anticancer synergy effect of SM and sorafenib in HCC.